Effectiveness of Minimum Wage Policy Implementation and Poverty Alleviation: A Public administration Analysis in Banten Province - Nindi Riyan Gustin; Nico Pranata Mulya (Faculty of Social Science, Universitas Negeri Padang, 2025)
This study evaluates the effectiveness of minimum wage policy implementation from a public administration perspective, focusing on poverty alleviation outcomes in Banten Province during 2013-2023. Through quantitative analysis of time-series data, the research examines how administrative mechanisms and governance structures influence policy outcomes. The findings reveal that minimum wage policy administration significantly impacts poverty thresholds (b = 0.181, p ¡ 0.01), while administrative efforts in unemployment management and economic growth initiatives show less pronounced effects. The strong model fit (R² = 0.966) provides crucial insights for public administrators regarding policy implementation effectiveness. Results indicate that successful poverty alleviation requires improved administrative coordination, enhanced policy monitoring systems, and strengthened government frameworks. This study advances public administration theory by providing empirical evidence on policy implementation effectiveness and offers practical recommendations for improving regional governance in poverty alleviation programs. The research contributes to public administration literature by demonstrating how quantitative analysis can inform better policy implementation and governance strategies